Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/ijms21165819
|View full text |Cite
|
Sign up to set email alerts
|

Becoming Stressed: Does the Age Matter? Reviewing the Neurobiological and Socio-Affective Effects of Stress throughout the Lifespan

Abstract: Social and affective relations occur at every stage of our lives. Impairments in the quality of this “social world” can be exceptionally detrimental and lead to psychopathology or pathological behavior, including schizophrenia, autism spectrum disorder, affective disorders, social phobia or violence, among other things. Exposure to highly stressful or traumatic events, depending on the stage of life in which stress exposure occurs, could severely affect limbic structures, including the amygdala, and lead to al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 128 publications
1
11
0
Order By: Relevance
“…Unlike previous studies that did not find a correlation of Hb volume and age [ 21 , 22 ], this study showed that the older the individuals in the depressed group, the smaller the volume. The older the patients with MDD, the more likely they are to live in isolation, have less interpersonal contact, and have a higher likelihood of physical illness [ 53 ], which may lead to a smaller whole Hb volume. To our knowledge, there are no research results that clearly demonstrate a correlation between Hb volume and duration of education or antidepressant medication use.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike previous studies that did not find a correlation of Hb volume and age [ 21 , 22 ], this study showed that the older the individuals in the depressed group, the smaller the volume. The older the patients with MDD, the more likely they are to live in isolation, have less interpersonal contact, and have a higher likelihood of physical illness [ 53 ], which may lead to a smaller whole Hb volume. To our knowledge, there are no research results that clearly demonstrate a correlation between Hb volume and duration of education or antidepressant medication use.…”
Section: Discussionmentioning
confidence: 99%
“…The exposure to chronic stress can lead to an altered balance between excitatory and inhibitory neurotransmission ( Page and Coutellier, 2019 ) and constitutes a predisposing factor for the development of different psychiatric disorders ( McEwen, 2000 ). Interestingly, the brain response to chronic stress is also influenced by the age of the individuals and their sex ( Hodes and Epperson, 2019 ; Spear, 2000 ; Mañas-Ojeda et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Anxiety, along with associated disorders such as post-traumatic stress disorder (PTSD), have in recent years been strongly associated with premature aging conditions [150][151][152][153]. With respect to the impact of RXFP3 upon anxiety-related disorders, it has been shown that specific central stimulation generates an anxiolytic effect in model organisms [154]. While acute effects of RXFP3 stimulation can generate anxiolytic effects, it has recently been shown that chronic localized RXFP3 stimulation instead can actually promote anxiety behavior [26].…”
Section: Anxiety and Post-traumatic Stress Disordermentioning
confidence: 99%